Teaching history for the common good - Barton, Keith C. (Lawrence Erlbaum Associates, 2004)
Barton and Levstik present a clear overview of competing ideas among educators, historians, politicians, and the public about the nature and purpose of teaching history, and they evaluate these debates in light of current research on students' historical thinking.